2010
DOI: 10.1111/j.1467-971x.2010.01642.x
|View full text |Cite
|
Sign up to set email alerts
|

Chinese perceptions of Inner Circle varieties of English

Abstract: Research from populations around the world on attitudes to varieties of English is essential in order to have a better understanding of how the complexities of globalization play a role in the form of English as a world language. To that end, university students in China were asked to name countries around the world where they believe English is spoken and indicate what kind of impression they have of those varieties without the presentation of voice stimuli. This type of data elicitation enables the participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Although some scholars claim that Japan has rejected (cultural) Westernisation (Hashimoto, 2007), it is still true that English language learning has been promoted extensively and that many people, including students and businesspeople, go to a private English conversation school to learn eikaiwa, 'conversational English' (McKenzie, 2008b, p. 275). While it seems natural that these respondents would draw on second language learning experiences to carry out the task in this survey, ease of understanding/learning was not a salient issue for Chinese university students surveyed (Evans, 2010;Garrett, 2009). A potential explanation for this discrepancy may be due to the intense English language learning situation in Japan described above.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although some scholars claim that Japan has rejected (cultural) Westernisation (Hashimoto, 2007), it is still true that English language learning has been promoted extensively and that many people, including students and businesspeople, go to a private English conversation school to learn eikaiwa, 'conversational English' (McKenzie, 2008b, p. 275). While it seems natural that these respondents would draw on second language learning experiences to carry out the task in this survey, ease of understanding/learning was not a salient issue for Chinese university students surveyed (Evans, 2010;Garrett, 2009). A potential explanation for this discrepancy may be due to the intense English language learning situation in Japan described above.…”
Section: Discussionmentioning
confidence: 98%
“…As indicated above, previous research has reported that these comments are usually reserved for UK English and not typically associated with US English. In addition, Chinese respondents did not show a similar attribution of US English being the 'original' version of English (Evans, 2010;Garrett, 2009).…”
Section: Usamentioning
confidence: 93%
“…Generally, research on the use of English at Chinese universities have remained focused on attitudes of Chinese learners towards various English varieties (e.g. Kirkpatrick and Xu ; Gao et al ; Hu ; ; Young ; Fong ; He and Li ; Evans ), and this study aims to provide what appears to be much needed sociolinguistic data on the actual use of English at Chinese universities (Bolton , Bolton and Graddol )…”
Section: The Research Designmentioning
confidence: 99%
“…Furthermore, Munro [13] studied international graduate students' views toward English and found their positive attitude toward American English. There have also been quite a few studies revealing student participants' favorable attitudes toward other native speaker models, such as British English [16,17]. The findings of substantial relevant research studies also show nonnative English speakers' general preference for native speaker models, as it was found in Jenkins's [22].…”
Section: A Discussionmentioning
confidence: 74%
“…Interestingly, the most preferred variety in native speaker models is not necessarily American English. Contrararily, Evans' [16] study, which examined 247 Chinese university students' views of the English varieties, shows American English is not likely to be a model considered -standard‖ among all. In Ladegaard and Sachdev [17], which examined perceptions of different English varieties, British English (RP) was rated the highest in terms of performance model.…”
Section: B Related Researchmentioning
confidence: 99%